For the function \( f \), given below, find the antiderivative \( F \) that satisfies \( F(1)=1 \). \( f(x)=x^{6}-3 x^{-4}+5 \) The antiderivative that satisfies the given condition is \( F(x)=\square \).
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To find the antiderivative \( F(x) \) of the function \( f(x) = x^{6} - 3x^{-4} + 5 \), we can integrate term by term: \[ F(x) = \int f(x) \, dx = \int (x^{6} - 3x^{-4} + 5) \, dx \] Calculating this, we have: \[ F(x) = \frac{x^{7}}{7} + 3x^{-3} + 5x + C \] Now, we need to determine the constant \( C \) to satisfy the condition \( F(1) = 1 \): \[ F(1) = \frac{1^{7}}{7} + 3(1^{-3}) + 5(1) + C = \frac{1}{7} + 3 + 5 + C \] This simplifies to: \[ F(1) = \frac{1}{7} + 8 + C = \frac{1}{7} + \frac{56}{7} + C = \frac{57}{7} + C \] Setting this equal to 1: \[ \frac{57}{7} + C = 1 \] To isolate \( C \): \[ C = 1 - \frac{57}{7} = \frac{7}{7} - \frac{57}{7} = -\frac{50}{7} \] Thus, substituting \( C \) back into \( F(x) \): \[ F(x) = \frac{x^{7}}{7} + 3x^{-3} + 5x - \frac{50}{7} \] So the antiderivative that satisfies the given condition is: \[ F(x) = \frac{x^{7}}{7} + 3x^{-3} + 5x - \frac{50}{7}. \]